Demonstration of Non-Hermitian Symmetry (NHS) IFFT/FFT Size Efficient OFDM Non-Orthogonal Multiple Access (NOMA) for Visible Light Communication - Assaidah Adnan; Yang Liu; Chi-Wai Chow; Chien-Hung Yeh (IEEE Photonics Journal, 2020)
We propose and experimentally demonstrate a non-orthogonal multiple access (NOMA) visible light communication (VLC) system using non-Hermitian symmetry (NHS) inverse-fast-Fourier-transform (IFFT)/FFT size efficient (SE) orthogonal frequency division multiplexing (OFDM). Fix power allocation and successive interference cancellation (SIC) algorithms are realized. The power ratio between different users, transmission distance, network cell coverage are investigated. The proposed scheme is also compared with the HS based direct-current optical (DCO)-OFDM NOMA-VLC system.